Karakterisasi hasil quenching besi cor pada manufaktur roda gigi mesin tenun - Andika Wisnujati; Mirza Yusuf; Dhini Fatimah (TURBO [Tulisan Riset Berbasis Online], 2021)
The development of science and technology today has a significant influence on technological development and advances in the industrial world. Casting is a product manufacturing technique in which the metal is melted in a furnace and then poured into a mold cavity that is similar to the original form of the cast product to be made. One of the results or products produced from the casting method in this study is a weaving gear component. The gear serves as a short distance power transmission based on the rotation ratio from the main shaft to the drive shaft. This study purpose to determine the effect of the quenching process with oil cooling media on cast iron material. The testing results reveal that the composition test results in 3.18% carbon content, such that the components in this gear manufacturing are used in cast iron, which essentially has the characteristics of being heat-resistant and brittle. It is also necessary to use it as a way of producing materials feeling the continuous impact. The brittling effect of quenching oil heat treatment improves the quality of the materials. It is observed from the research findings that use the Vickers hardness test that the quenching heat treatment shows a substantial difference in score. The highest Vickers hardness test score with quenching oil materials achieving a score of 427.84 VHN is seen. The test exhibits the maximum value of 378.18 VHN in raw materials.Keywords: Cast iron, quenching, chemical composition, Vickers hardness.